Pemanfaatan Hasil Induksi Hormon Estrogen Terhadap Kadar Estradiol dan Histologi Uterus Mencit (Mus musculus) Sebagai Buku Suplemen Sistem Reproduksi di SMA - Erlia Narulita; Jekti Prihatin; Ratna Sari Dewi (JURNAL BIOEDUKATIKA, 2016)
Synthetic estrogen hormone that has known by the public is an estrogen that is contained in hormonal contraception or birth control pills. The lack of public knowledge about the action mechanism of oral contraception on the reproductive organs makes people ignoring about the impact of it. This study was conducted to analyze the differences in the induction of estrogen towards the levels of estradiol and histology of the uterus and its utilization as a supplement book of Reproductive System topic in high school. Balb-C female mices were used as the tested animals and Microgynon, the contraceptive pillas trademark was used as a source of estrogen induces. Blood samples were taken at pro-estrus phase, while the uterus was taken at each phase of the estrous cycle. Measurement of estradiol levels was done by ELISA method, whereas the thickness of endometrium is determined on a longitudinal incision of the uterus by the method of preparation of histological paraffin and HE staining. The supplement book was arranged refers to 4-D models. The results showed that there was a difference between the levels of estradiol-induced estrogen treatment with control, but in endometrial thickness among the control treatment with estrogen did not show the differences significantly. The results also showed that the estrogen induction has no significant effect on endometrium thickness at each phases of estrous cycle. The results of research were used as supplement book and it can be used for enriching knowledge of reproductive topic on high school.